The Contribution of Computer in Dentistry Advancement: A Review - Yousif, 1Mogahid Abdelrahman; Elbashir, Murtada Khalafallah (Gezira Journal of Engineering and Applied Sciences, 2015)
Computer is basically an electronic device which can convert data into information at a very high speed and in a reliable and accurate way. It has a large and perfect memory that enables it to handle large volumes of data and analyze it to come up with logical decisions. Computer also has been applied in various medical fields. In this paper we discuss its application in preventive and curative dentistry, where it becomes a powerful tool in educational dentistry, surgery, radiology.